Theory And Practice Of Mediation In The Indigenous Peoples Of Aceh - Gayo, Sabela (Legalpreneur Journal, 2025)
This paper discusses the theory and practice of mediation in the indigenous peoples of Aceh, which is known to have a dispute resolution system based on deliberation and kinship. This study uses a qualitative approach to the method of literature study and observation of mediation practices in several villages in Aceh. It was found that customary mediation practices in Aceh not only promote conflict resolution, but also restore social relations. This local wisdom has historically grown out of the social structure of Acehnese society and has a meeting point with the national legal system, especially in the settlement of civil and minor criminal cases. This article also examines the challenges of harmonization between customary law and national law.